Comparison of efficacy in terms of prevention of preeclampsia in patients with calcium intake versus without calcium intake - Beena Rehman, Khadija Akbar, Irum Ibraheem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy in term of prevention of preeclampsia in patients with calcium intake versus without calcium intake Materials & Methods: Between April 2021 to October 2021, total 212 Women between 18-35 years of age, having 20 weeks of gestation assessed on LMP, normal blood pressure, no peripheral edema and no proteinuria, women with singleton pregnancy and patients upto para-5 were selected from Department of Obstetrics & Gynecology, MMC General Hospital Peshawar for this randomized controlled trial. Calcium was given to group A while group B was given only routine food. Prevention of preeclampsia in patients with calcium intake versus without calcium intake was assessed. Results: In group A (calcium intake group) & B (without calcium intake group) mean age was 23.15 ± 6.68 years and 23.41 ± 6.05 years respectively. The mean gestational age in group A was 34.71 ± 4.73 weeks and in group B was 33.42 ± 4.83 weeks. There was development of pre-eclampsia in 07 (6.60%) patients and no pre-eclampsia in 99 (93.40%) patients in Group A, in Group B, it was noted in 19 (17.92%) and 87 (82.08%) patients respectively (p=0.012). Conclusion: This study concluded that calcium intake during pregnancy is associated with higher efficacy in preventing pre-eclampsia compared to those without calcium intake. Keywords: Calcium supplementation, proteinuria, high blood pressure.